211k views
10 votes
100 points PLEASE ANSWER ASAP thank you so much

100 points PLEASE ANSWER ASAP thank you so much-example-1
User Luanne
by
5.0k points

2 Answers

1 vote

LHS

  • (a+bi)²
  • (a+bi)(a+bi)
  • a²+b²i²+2abi
  • a²-b²+2abi

RHS

  • (a+b)(a-b)+2abi
  • a²-b²+2abi

Hence verified

User Mekka
by
4.4k points
4 votes

Answer:


\textsf{Apply the Perfect Square Formula}\quad (a + b)^2 = a^2 + 2ab + b^2:


\implies (a+bi)^2=a^2+2abi+(bi)^2


\textsf{Apply exponent rule} \quad (a\cdot b)^c=a^cb^c:


\implies a^2+2abi+b^2i^2


i=√(-1) \implies i^2=-1


\textsf{Apply imaginary number rule} \quad i^2=-1:


\implies a^2+2abi+b^2(-1)


\implies a^2+2abi-b^2


\textsf{Collect the real parts:}


\implies a^2-b^2+2abi


\textsf{Factor the real parts by applying the Difference of Two Squares Formula}\\x^2-y^2=(x+y)(x-y) :


\implies (a+b)(a-b)+2abi

User Gyromonotron
by
5.1k points